Mouse in Saami and Related Problems - Krzysztof Tomasz Witczak (Oficyna Wydawnicza ATUT, 2024)
The article discusses Saami terms for “mouse” (e.g. Northern Saami “sáhpán”, Inari Saami “säplig”, Pite Saami “saahpìek”), explaining them as a common heritage of Uralic origin. It is suggested that the related words are to be found in Selkup Samoyed and Kolyma Yukaghir with the meaning “squirrel” or “flying squirrel”, as well as in Ugric. The present author explains semantic aspects of this comparison and presents similar instances attested in the Uralic languages, e.g. Khanty “aj-ʌanki” “mouse” (originally “small squirrel”). It is additionally concluded that the Proto-Finno-Ugric term for “mouse”, *šiŋirɜ, must be related to Proto-Samoyed *tə̑ rä- “squirrel”.